Methodology in Subliminal Psychodynamic Activation: The Next Step in the Debate - Birgegård, Andreas; Sohlberg, Staffan (Perceptual and motor skills, 2001)
Subliminal psychodynamic activation methodology has recently been the subject of an exchange of views between Birgegärd and Sohlberg (1999) and Fudin (2000). The agreements and some remaining points of contention are summarized here. The main difference of opinion appears to concern unconscious verbal encoding in relation to subjective experience in subliminal stimulation and whether subliminal psychodynamic activation results are unreliable until a full explanation of how verbal encoding works is at hand. We conclude that clarifying perspectives is important and that those suggesting alternative explanations of results on subliminal psychodynamic activation must now empirically investigate their claims.